Inheritance of coffee leaf rust resistance in Timor Hybrid UFV 443-03 - Capucho, Alexandre Sandri; Caixeta, Eveline Teixeira; Zambolim, Eunize Maciel; Zambolim, Laércio (Pesquisa Agropecuaria Brasileira, 2010)
The aim of this work was to characterize the resistance inheritance of the Timor Hybrid UFV 443-03 to coffee leaf rust (Hemileia vastatrix). For this, the race II and pathotype 001 of coffee leaf rust were inoculated in 246 F2 plants, 115 susceptible backcrossing (BCS) plants, and 87 resistant backcrossing (BCR) plants, derived from the crossing between the susceptible genotype 'Catuaí Amarelo' IAC 64 and the resistance source Timor Hybrid UFV 443-03. For both inoculums, the 'Catuaí Amarelo' IAC 64 was susceptible, while the Timor Hybrid, the plant representing F1 generation, and the BCR plants were resistant. The F2 plants inoculated with race II presented two significant segregation ratios: 15:1 and 61:3. The resistance inheritance was verified by the inoculation of the BCS plants, which segregated at a 3:1 ratio, an expected pattern for the inheritance controlled by two genes, whereas the segregation hypothesis of 7:1 for three genes was rejected. Two independent and dominant genes confer the genetic resistance of Timor Hybrid UFV 443-03 to race II and pathotype 001 of H. vastatrix.